Przyżyciowa ocena pęcherzyka filtracyjnego na poziomie komórkowym za pomocą HRT II Cornea Module - Jurowska-Liput, Joanna; Krzyżanowska, Patrycja; Szelepin, Łukasz; Niżankowska, Maria Hanna (Klinika Oczna / Acta Ophthalmologica Polonica, 2008)
Purpose: Evaluation on the cellular level the filtering bleb following trabeculectomy, using the HRT II Cornea Module. Material and methods: Confocal microscopy was performed in 47 eyes following trabeculectomy to state typical images for functioning blebs with no MMC application, with MMC application and non-functioning blebs. In gathered images we assessed appearance, size and number of intraepithelial microcysts, encapsulation, density of subepithelial tissue and blood vessels. Results: A large number of microcysts filled with fluid and loosely arranged subepithelial tissue were observed in functioning blebs with no MMC application (20 eyes). Smaller amount of microcysts but their larger size and inflammatory cells were typical for functioning blebs with MMC application (18 eyes). We found encapsulated microcysts and dense connective tissue in non-functioning blebs (9 eyes). Conclusions: Visualization of filtering bleb structure in vivo is an objective and helpful method of evaluation of functioning status following trabeculectomy.